Characteristics of incarcerated women's participation in groups: Exploring the Programme for the International Assessment of Adult Competencies United States prison dataset - Hicks-Becton, Latasha Y. (Journal of addictions & offender counseling, 2023)
This study employs logistic regression and latent class analyses to explore the relationship between incarcerated women's (n = 252) participation in nonacademic prison groups/skills classes and their demographic (e.g., education) and prison context (e.g., time to release) characteristics, using the 2014 Programme for the International Assessment of Adult Competencies United States prison dataset. Time to release was a significant factor in readiness class participation. Time to release and race/ethnicity were significant factors in addiction group participation. Education level had the largest effect size across all groups/classes explored. We discuss counseling implications for using group/class screening to connect with incarcerated women, especially those with intersecting and historically marginalized identities.